Dato' Haji Sidek Haji Jamil / Nurul Nadrah Abdul Kader, Nur Shahidah Mohamad Ali and Siti Hajar Mat Arsat - Abdul Kader, Nurul Nadrah; Mohamad Ali, Nur Shahidah (2011)
Dato 'Haji Sidek bin Haji Jamil is a former Director General of the National Archives. He started his career in the field of archives from 1974 to present. Throughout his involvement in this field, he was awarded several honorary awards for significant contributions that have been given by him. Contributions made by him not only in the country but have reached up to international level. Throughout his involvement in this field, namely from 1974 until now, he has contributed many ideas and best service. He also contributed a lot of energy and screaming pain in upholding the National Archives. Among them are, he is often chosen as a representative of a meeting or conference at the international level. In addition, he is also heavily involved in presenting papers are held in and outside the country. He is also part of the board of directors and the many contributions in the field outside the department either within or outside the country.